Challenges Encountered by Indigenous Youth in Postsecondary Education - Chichekian, Tanya; Bragoli-Barzan, Léa (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2020)
This paper explores the need to build a reciprocal partnership with Indigenous Peoples and develop culturally-relevant strategies that foster academic motivation among Indigenous youth. The objectives of this study were to describe education professionals’ perceptions regarding: (1) the challenges Indigenous students face when transitioning to postsecondary education, (2) strategies used to provide academic support, and (3) the different ways of enhancing Indigenous students’ educational experiences. These perceptions were necessary to better comprehend the ongoing progress related to the need for a decolonized education within academic institutions. Although an increasing proportion of Indigenous Peoples are obtaining college diplomas, some challenges remain and are specifically encountered during Indigenous students’ transition to postsecondary education and in the cultural relevance within their learning materials.